Green R&D versus End-of-Pipe Emission Abatement: A Model of Directed Technical Change - Michael Rauscher (Verein für Socialpolitik, 2010)
The paper looks at a model of directed technical change in an environmental-economics context. Firms can do conventional or green R&D or they can abate emissions at the end of pipe. The paper has two main foci. On the one hand, it investigates the impact of environmental regulation on the allocation of resources to conventional R&D, green R&D, and end-of-pipe abatement. On the other hand, it addresses the question whether stricter emission standards should be used to support green R&D and/or economic growth. The analysis looks at the steady state and finds that stricter environmental regulation reduces economic growth. It, however, may induce a shift from end-of-pipe abatement to process-integrated green technologies. As regards optimal policies, the first best is to use a Pigouvian tax to internalise environmental externalties and R&D subsidies to internalise knowledge spillovers. A second-best environmental policy in the absence of R&D subsidies may be stricter than the first-best benchmark if knowledge spillovers in the development of green technologies are larger than in the rest of the economy. Otherwise, the second-best environmental policy will always use laxer standards.
Keywords: O41; Q55; O38; 330; economic growth and the environment; directed technical change